Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s10336-014-1139-4
|View full text |Cite
|
Sign up to set email alerts
|

The function of seasonal song in a tropical resident species, the Red-throated Ant-tanager (Habia fuscicauda)

Abstract: Recent studies of tropical birds with year-round territoriality indicate that song rate is relatively low yearround in association with lower seasonality and relatively stable social environment over the year. We examined seasonal variation in the song rate of Red-throated Anttanagers (Habia fuscicauda), a socially monogamous species in which males predominantly sing during the breeding season, to determine to what extent increased song rate is driven by (1) increased territory defense, (2) pair coordination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…In other words, if male song increases primarily as a result of territorial defense, then seasonal song activity should be positively correlated with the territorial intrusions and escalated aggressions (Chiver et al, 2015). Such results have been reported in Song sparrows (Hyman, Hughes, Searcy, & Nowicki, 2004;Nowicki, Searcy, Krueger, & Hughes, 2002).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In other words, if male song increases primarily as a result of territorial defense, then seasonal song activity should be positively correlated with the territorial intrusions and escalated aggressions (Chiver et al, 2015). Such results have been reported in Song sparrows (Hyman, Hughes, Searcy, & Nowicki, 2004;Nowicki, Searcy, Krueger, & Hughes, 2002).…”
Section: Discussionsupporting
confidence: 65%
“…Despite the fact that many bird species are residents of tropical habitats, so far no avian species from Indian subcontinent has been studied to provide evidence that song can escalate response by a territory owner (Chiver, Stutchbury, & Morton, 2015;Stutchbury & Morton, 2001). Given this limitation in studying birds from only limited areas, and with the goal of providing new evidence from an unstudied species we performed a field experiment using the combination of existing playback methods and the use of a crafted model of the study species (the Pied Bush Chat).…”
mentioning
confidence: 99%
“…Under these conditions, it is generally expected that singing activity is relatively constant year-round and that song is also used outside of the breeding context for territory defence (Tobias et al 2011, Topp & Mennill 2008). However, recent studies on several Neotropical species have indicated that singing activity varies throughout the year – males sing infrequently outside of the breeding season and increase their singing activity dramatically during the breeding period (Chiver et al 2015, Hill et al 2015, Koloff & Mennill 2013). Song, often performed by both sexes, also functions in stimulation of the social mate and helps in within-pair timing and the synchronization of nesting in the tropics (Chiver et al 2015, Kunkel 1974).…”
Section: Introductionmentioning
confidence: 99%
“…84 85 It is generally assumed that most birds from the temperate zone exhibit marked seasonal 86 whereas others show markedly seasonal patterns of vocal activity correlated with 93 reproduction (e.g., Negret et al 2015;Stutchbury & Morton 2001). Even in species that 94 sing constantly during the year, vocal activity may vary seasonally, increasing during the 95 breeding period (e.g., Koloff & Mennill 2012;Chiver et al 2015). 96…”
Section: Introduction 50mentioning
confidence: 99%